Inkjet‐Printed Piezoelectric Thin Films for Transparent Haptics. Issue 8 (9th April 2022) - Glinsek, Sebastjan; Song, Longfei; Kovacova, Veronika; Mahjoub, Mohamed A.; Godard, Nicolas; Girod, Stéphanie; Biagi, Jean‐Luc; Quintana, Robert; Schleeh, Thomas; Guedra, Matthieu; Rupin, Matthieu; Defay, Emmanuel
Abstract: Transparent thin‐film piezoelectric transducers are attractive for haptic displays. However, for their widespread use in consumer electronics, innovative and cost‐effective processing methods need to be developed. In this contribution the effectiveness of the deposition of lead zirconate titanate thin films by inkjet printing for the fabrication of haptic devices is demonstrated. The 1, 3‐propanediol solvent is used to prepare effective inkjet‐printing inks from chemical solution deposition solutions. The printed thin‐film structures on fused silica glass substrates are 900 nm thick and strongly {100} oriented perovskite phase is detected in X‐ray diffraction patterns. To fabricate devices, interdigitated capacitors and SU‐8 insulation layers are deposited on top of the printed lead zirconate titanate. Dimensions of the final device are 15.7 × 3.4 mm 2 . A standing antisymmetric Lamb wave is observed at 63.3 kHz, with out‐of‐plane displacement reaching 2 µm at an applied voltage of 100 V. This value exceeds the limit at which the texture rendering function can be induced in the device. Good functional performance of the device is linked with good electromechanical properties of the printed piezoelectric, with permittivity ε ′ and piezoelectric coefficient e 33, f values of 1000 and 7.7 C m −2, respectively, which are comparable to films prepared by standard spin‐coating process. Abstract : Effectiveness of inkjet printing of piezoelectric thin films for haptic devices is demonstrated. A transparent device, based on printed piezoelectric lead zirconate titanate and interdigitated indium tin oxide electrodes, exhibit a standing Lamb wave at 63.3 kHz, with out‐of‐plane displacement reaching 2 µm at an applied voltage of 100 V. The performance is comparable to spin‐coated devices.